Photonic integrated circuits development: a universal transceiver for NG-PON2 - Ferreira, Ana Rita Rodrigues (2015)
In the last years there has been a clear evolution in the world of telecommunications, which goes from new services that need higher speeds and higher bandwidth, until a role of interactions between people and machines, named by Internet of Things (IoT). So, the only technology able to follow this growth is the optical communications. Currently the solution that enables to overcome the day-by-day needs, like collaborative job, audio and video communications and share of les is based on Gigabit-capable Passive Optical Network (G-PON) with the recently successor named Next Generation Passive Optical Network Phase 2 (NG-PON2). This technology is based on the multiplexing domain wavelength and due to its characteristics and performance becomes the more advantageous technology. A major focus of optical communications are Photonic Integrated Circuits (PICs). These can include various components into a single device, which simpli es the design of the optical system, reducing space and power consumption, and improves reliability. These characteristics make this type of devices useful for several applications, that justi es the investments in the development of the technology into a very high level of performance and reliability in terms of the building blocks. With the goal to develop the optical networks of future generations, this work presents the design and implementation of a PIC, which is intended to be a universal transceiver for applications for NG-PON2. The same PIC will be able to be used as an Optical Line Terminal (OLT) or an Optical Network Unit (ONU) and in both cases as transmitter and receiver. Initially a study is made of Passive Optical Network (PON) and its standards. Therefore it is done a theoretical overview that explores the materials used in the development and production of this PIC, which foundries are available, and focusing in SMART Photonics, the components used in the development of this chip. For the conceptualization of the project di erent architectures are designed and part of the laser cavity is simulated using Aspic™. Through the analysis of advantages and disadvantages of each one, it is chosen the best to be used in the implementation. Moreover, the architecture of the transceiver is simulated block by block through the VPItransmissionMaker™ and it is demonstrated its operating principle. Finally it is presented the PIC implementation.